2017
DOI: 10.20324/nelumbo/v59/2017/120460
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Ecology of Soil Algae in Broadleaf Sacred Grove and Pine forest in East Khasi Hills, Meghalaya

Abstract: In the present study, soil algal community inhabiting in two different forest types i.e., pine forest and subtropical broadleaf forest (Mawphlang sacred grove) in East Khasi Hills District of Meghalaya have been investigated. Light availability to the forest floor and soil physico-chemical parameters were examined. A total of 124 taxa of soil algae were recorded from both the forests. Members from Chlorophyta, Xanthophyceae, Eustigmatophyceae contributed the most (72%-80%). Mawphlang sacred grove was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…Cyanobacteria in forest algal communities range from 2.7% to 15.7% of the total number of species. The data obtained are generally consistent with the results of other researchers of algae in forest ecosystems, which indicate that the main forest communities of algae are Chlorophyta and Xanthophyceae [47][48][49]. It should be noted that the role of green algae and Xanthophyceae in the formation of communities differs in various types of forest.…”
Section: Resultssupporting
confidence: 90%
“…Cyanobacteria in forest algal communities range from 2.7% to 15.7% of the total number of species. The data obtained are generally consistent with the results of other researchers of algae in forest ecosystems, which indicate that the main forest communities of algae are Chlorophyta and Xanthophyceae [47][48][49]. It should be noted that the role of green algae and Xanthophyceae in the formation of communities differs in various types of forest.…”
Section: Resultssupporting
confidence: 90%
“…Both season and forest types had significant effects on soil algae in our study area (Dirborne and Ramanujam, 2017). Liquidambar formosana plantation has highest algal diversity due to the influence of light, which is consistent with Neustupa and Skaloud (Neustupa and S ̌kaloud, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the change of temperature would affect the dynamics of soil physicochemical properties and the nutrient cycles, which indirectly affects the growth and reproduction of algae. Many environmental factors affect the diversity of soil algal community, such as moisture content, pH, and NH 4 + −N (Zancan et al, 2006;Dirborne and Ramanujam, 2017;Agha et al, 2020). In the present study, spearman's correlation analyses showed that soil moisture content was significantly and positively correlated with observed species and Shannon index (p< 0.01).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations